John Adams Kingsbury papers - Kingsbury, John Adams, 1876-1956.; Kingsbury, John Adams, 1876-1956.; Kingsbury, John Adams, 1876-1956.
Correspondence, journals and diaries, family papers, autobiographical material, travel notes, manuscripts of and other material relating to Kingsbury's books, Health in Handcuffs (1939) and Red Medicine (1933), speeches and articles, news releases, legal and financial papers, newspaper clippings, and memorabilia.
Kingsbury's professional papers (1907-1939) including correspondence, financial papers, reports, and other business records are primarily associated with his attendance at Columbia University Teachers College, his service as assistant secretary of the State Charities Aid Association in New York from 1907 to 1911, director of the New York Association for Improving the Condition of the Poor (1911-1914), and Commissioner of Public Charities of New York City during the administration of John Purroy Mitchel (1914-1918).
Includes material on other organizations with which Kingsbury was affiliated such as the American Council on Soviet Relations, America-Yugoslav Society of New York, American Association of the Red Cross, Milbank Memorial Fund, Progressive Party, Serbian Child Welfare Association of America, U.S. Work Projects Administration, and Young Men's Christian Association of the City of New York. Topics include agriculture, American-Soviet and American-Yugoslav relations, astronomy, Chinese life and culture, Eastern European relief efforts, group health insurance, multiple sclerosis, mushrooms, New Deal legislation, public health in America and the Soviet Union, socialist societies, socialized medicine, travel, tuberculosis, unemployment, venereal disease, war relief, welfare, and world peace.
Correspondents include Jane Addams, Alexander Graham Bell, Louis Dembitz Brandeis, Charles C. Burlingham, Bailey B. Burritt, Mary E. Dreier, Paul De Kruif, Albert Einstein, Homer Folks, Harry Lloyd Hopkins, Elbert Hubbard, Charles Evans Hughes, Harold L. Ickes, Walter Lippmann, Jack London, Henry Morgenthau, Sir Arthur Newsholme, Frances Perkins, Gifford Pinchot, Jacob A. Riis, Raymond Robins, Franklin D. Roosevelt, Theodore Roosevelt, and William Henry Welch.
Library of Congress Prints and Photographs Division.
Social worker and social reformer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Addams, Jane, -- 1860-1935 -- Correspondence; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Burlingham, Charles C. -- 1858-1959 -- Correspondence; Burritt, Bailey B. -- 1878-1953 -- Correspondence; De Kruif, Paul, -- 1890-1971 -- Correspondence; Dreier, Mary E. (Mary Elisabeth), -- 1875-1963 -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Folks, Homer, -- 1867-1963 -- Correspondence; Hopkins, Harry L. -- 1890-1946 -- Correspondence; Hubbard, Elbert, -- 1856-1915 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Lippmann, Walter, -- 1889-1974 -- Correspondence; London, Jack, -- 1876-1916 -- Correspondence; Mitchel, John Purroy, -- 1879-1918.; Morgenthau, Henry, -- 1856-1946 -- Correspondence; Newsholme, Arthur, -- Sir, -- 1857-1943 -- Correspondence; Perkins, Frances, -- 1880-1965 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Riis, Jacob A. -- 1849-1914 -- Correspondence; Robins, Raymond, -- 1873-1954 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Welch, William Henry, -- 1850-1934 -- Correspondence; New York (N.Y.). -- Department of Public Charities and Correction; United States. -- Work Projects Administration; American Association of the Red Cross; American Council on Soviet Relations; Columbia University. -- Teachers College; Milbank Memorial Fund; New York Association for Improving the Condition of the Poor; Serbian Child Welfare Association of America; State Charities Aid Association (N.Y.); Young Men's Christian Association of the City of New York; Agriculture; Astronomy; Charities, Medical; Endowments; Health insurance; Medicine, Preventive; Men -- Societies and clubs; Multiple sclerosis; Mushrooms; New Deal, 1933-1939.; Peace; Poverty; Public health; Public health -- Russia; Public service employment; Public welfare; Public welfare -- New York (State); Sexually transmitted diseases; Socialism -- Societies, etc; Tuberculosis; Unemployment; Voluntary health agencies; Voyages and travels; War relief; World War, 1939-1945 -- War work